Innovatorium: En arena för långsiktig strategisk produktplanering - Hagman, Max; Jansson, Embla; Medailleu, Emelie; Pålsson, Edith; Razocky, Abbas; Xie, Sofia (My University, 2023)
This report deals with a project initiated by Volvo Group Trucks Technology, also referred to as Volvo GTT, whose purpose is to investigate problem areas and needs related to the company's future planning. Currently, the company experiences that there is a lack of established strategies for development processes that target the period between today’s concepts and future visions. They therefore request an arena, that in this report has been named Innovatorium, that will promote such strategies. The goal of this project is thus to develop a conceptual solution that supports and promotes Volvo GTT:s continued innovation work for future planning. With a comprehensive problem analysis as a starting point, a thorough needs identification was conducted using interviews, observations and literature studies. Subsequently, idea generation and concept development were performed based on both the needs identification and additional user testing. Design decisions have been based on both independent exploration and existing research in the field. The literature studied covers areas related to innovation and future work, including trends, and their role in future work, but also how factors such as creativity, collaboration, and utilization of information affect innovation work. The project has resulted in a conceptual solution as well as potential areas for further development that will serve as support and foundation for Volvo GTT, where the outcome addresses both the environment and tools within an innovation process. The project’s result appear to support an innovation process by promoting creativity, collaboration and diversity as well as being adaptable to different individuals and the present time they find themselves in